Open reduction and internal fixation of a distal clavicle fracture using a clavicle hook plate - Nett, Matthew H. (Radiol Case Rep, 2015)
Historically, fractures of the clavicle have been treated nonoperatively. However, it is becoming much more common for orthopedic surgeons to treat clavicle fractures with open reduction and internal fixation–particularly fractures of the lateral clavicle with high rates of nonunion, such as the Neer type II. Several techniques and devices are currently being used for clavicle fixation. We present a case of a recently developed and increasingly popular fixation device called a clavicle hook plate, used to repair a Neer type II clavicle fracture.